Learning of web application frameworks based on concerns, micro-learning and examples (2015)
Abstract: Web Applications Frameworks (WAFs) have become very popular tools for developing software applications. These tools lead to the implementation of a big amount of classes, components, and libraries which support developers for saving costs, time, and effort. Due to the big number of WAF elements, a developer needs to invest considerable effort and time in order to understand the WAF usage. Some authors had proposed different framework learning techniques, but these techniques focus on how to document or show the framework information. Then, how to drive the framework learning is a developer task. Commonly, developers follow a guide containing too much information, but in some cases developers only need to learn an incomplete WAF usage. We define in this thesis a list of WAF components, a list of web application concerns and a list of examples which create a new learning technique. This technique will indicate -based on the developers‘ requirements- the specific elements they should know to develop their applications. Saving time and acquiring WAF knowledge.